THEORETICAL AND PEDAGOGICAL FOUNDATIONS OF INCLUSIVE EDUCATION AND INCLUSIVE METHODOLOGICAL APPROACHES IN TEACHING PHYSICS - Sattorov Komronbek Samadjon o‘g‘li (Bright Mind Publishing, 2025)
This article analyzes the theoretical and pedagogical foundations of inclusive education, as well as methodological approaches to teaching physics in inclusive learning environments. The study is based on international frameworks such as the Salamanca Statement, UNESCO and UNICEF guidelines, and the UN Convention on the Rights of Persons with Disabilities, which emphasize equal access, reasonable accommodation, and full participation of learners with diverse needs. The paper examines the development stages of inclusive education—from segregation and integration to full inclusion—and highlights current reforms in Uzbekistan aimed at implementing inclusive practices in general education schools. The specific characteristics of physics as a highly abstract and conceptually demanding subject are discussed, with emphasis on the cognitive challenges faced by learners with special educational needs. The research identifies effective instructional methods, including differentiated instruction, multisensory teaching, cooperative learning, adapted assessment, and integration of digital technologies such as virtual laboratories and interactive simulations. The pedagogical principles of individualization, collaboration, environmental adaptation, and reflection are described as key to successful inclusive physics teaching. The conclusions stress that inclusive education enhances equity, accessibility, and the overall quality of physics learning for all students.
Keywords: Inclusive education, physics education, multisensory approach, differentiated instruction, adapted assessment, inclusive pedagogy, special educational needs, Uzbekistan education reforms.